(3GdLedI GdcGajI hGdfHPI GdTGajIs - (3eMeO Hf YHO GdeYWj GdKZQj, CHh YHO Gddgs ((3eMeO Hf Ydi Hf UGdM s)
(3ChdgG (B:s
(3GdMeO ddg LGYd GdMeO CaVd hUdI Edjg hHYO agPg LedI cGajI hfHPI TGajI jTWQ Edi GSJYeGdgG GdCOjH hJcajg Ef GbJUQ YdjgG LeYJgG dc ef eTGYjQ cJH GddZI hUMGMgG s
(3BNQgG (B:s
(3GdeGVjGf (B: (3GdSja hGdbOQ hGdhGbjGf (B: (3GdLO hGdXaQ ced LejY eG bjOJg dc ef GdahGFO , s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs